Identifikasi Asam Lemak Minyak Ikan Nila (Oreochromis niloticus), Hasil Permurnian Menggunakan Kombinasi Arang Aktif dan Bentonit - Sumartini; Supriyanto; Pudji Hastuti (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2019)
The fishery processing industry activities generally produce waste that is thrown away so that it does not experience reuse. The components of fish waste consist of the head, tail-bones, skin, and stomach contents that can be used as fish oil. The one of the problem in the use fish oil as a raw material for intermediate products is the difficulty in making a comparison ratio between fish oil and other ingredients, so we need to know the composition of fatty acids as a reference formulation for the application of waste utilization of tilapia oil. The method used is a quantitative method that is identifying fatty acids in tilapia oil. Data analysis uses Gas Chromatography (GC) as chromatogram data. Based on the results of the analysis that the composition of fatty acids from waste tilapia oil as follows: the dominant saturated fatty acids are palmitic fatty acids as much as 20.96%, the dominant monounsaturated fatty acids are oleic fatty acids as much as 22.63%, and fatty acids the dominant polyunsaturated fatty acid is linoleic as much as 16.77%. While the fatty acid components of EPA and DHA are found in very small quantities which is less than 0.01%.